SQSTM1/p62 in intrahepatic cholangiocarcinoma promotes tumor progression via epithelial–mesenchymal transition and mitochondrial function maintenance - Jiafeng Chen; Zheng Gao; Xiaogang Li; Yinghong Shi; Zheng Tang; Weiren Liu; Xin Zhang; Ao Huang; Xuanming Luo; Qiang Gao; Guangyu Ding; Kang Song; et al. (Cancer Medicine, 2023)
Abstract Background SQSTM1/p62 is a selective autophagy receptor that regulates multiple signaling pathways participating in the initiation and progression of tumors. Metastasis is still the main cause for intrahepatic cholangiocarcinoma (ICC)‐associated mortality. Hence, this study aimed to explore the mechanism of p62 promoting the progression of ICC. Methods Western blotting and immunohistochemical analyses were conducted to detect the expression level of protein p62 in ICC tissues and its correlation with prognosis. Subsequently, the loss‐of‐function experiments in vitro and in vivo were performed to define the role of p62 in ICC cell proliferation, invasion, and metastasis. Then, the effect of p62 knockdown on mitochondrial function and mitophagy was evaluated by measuring the oxygen consumption rate, and using immunofluorescence and western blotting analyses. Results The expression of p62 was significantly upregulated in ICC specimens compared with normal tissues. We further illustrated that p62 expression positively correlated with lymph node metastasis and poor prognosis. The loss‐of‐function assays revealed that p62 not only promoted ICC cell proliferation, migration, and invasive capacities in vitro, but also induced lung metastasis in the xenograft mouse model. Mechanistically, high expression of p62‐induced epithelial–mesenchymal transition (EMT) with the upregulation of Snail, vimentin, N‐cadherin, and downregulation of E‐cadherin. Moreover, the autophagy‐dependent function of p62 might play a vital role in maintaining the mitochondrial function of ICC by mitophagy which might further promote EMT. Conclusion These data provided new evidence for the mechanism by which abundant p62 expression promoted ICC progression, suggesting a promising therapeutic target for antimetastatic strategies in patients with ICC.